HEALTH AND ITS IMPORTANCE IN THE FAMILY CARE, EDUCATIONAL AND SOCIALIZATION PROCESS ON THE EXAMPLE OF THE FUNCTIONING OF PROFESSIONAL FOSTER FAMILIES IN SZCZECIN - Kazubowska, Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Health is in the area of analysis of many sciences, e.g. psychology, sociology, pedagogy or philosophy. Each of them presents health and its specificity in a specific way. The most frequently indicated dimensions of health are: physical, mental (including intellectual and emotional), social, spiritual and transcendent. Contemporary pedagogical concepts of health emphasize that they can be considered as: value, resource (wealth), means, aim, a concept emphasizing the benefits of being healthy. Attention is also paid to the health mandala and the eudaimonic concept of family health. Thanks to these concepts, health is part of family care, educational and socialization processes. Parents, the main implementers of integrated interactions, create, among others, health behaviors, attitudes or lifestyle of their children. The subject of the research was the course of care, educational and socialization processes in professional foster families functioning in the city of Szczecin. The aim of the research was to find out about the specificity of family care, educational and socialization processes. The activities of professional foster families in caring for: children's health, their health attitudes and behaviors as well as health as a value in human life were especially emphasized. The research method was to triangulate the diagnostic survey method with the qualitative dimension of the case study. The technique used for the study was a questionnaire, in-depth qualitative interview and direct observation. The obtained empirical material was subjected to an in-depth quantitative and qualitative analysis with elements of interpretability of the data, however, efforts are being made to make a holistic diagnosis of the family. Axiologization of health attitudes in the surveyed families and making children aware of the need to take care of their own health on the basis of resources at hand are particularly significant for the armory.